Microseismic sequences associated with rockbursts in the tunnels of the Jinping II hydropower station. (December 2015) - Feng, Guang-Liang; Feng, Xia-Ting; Chen, Bing-Rui; Xiao, Ya-Xun
Abstract: Microseismic (MS) monitoring techniques have been used to warn of rockbursts in tunnels to reduce rockburst risks and ensure safe construction with different degrees of success. In order to reveal the characteristics of MS activity in tunnel rockburst development processes, and lay a foundation for tunnel rockburst warning, MS sequences accompanying rockburst development processes in tunnels are studied in this paper. The study is based on tunnels (with a maximum burial depth of 2525 m) of the Jinping II hydropower station, China. Firstly, two MS parameters are put forward to express the comprehensive microseismicity and intensity of the MS events in the rockburst development process. Secondly, the laws governing the evolution of the two parameters are analyzed based on 44 moderate and intense immediate rockburst cases in the tunnels of Jinping II. Then, the MS sequences associated with immediate rockburst development processes in tunnels are divided into two types: fore-main and swarm shock MS sequences. The characteristics of the two types of MS sequences are different with each other. Finally, based on a theoretical analysis and verification using engineering examples, the mechanism of formation of the two MS sequences is analyzed. The fore-main MS sequences are mainly controlled by excavation unloading in the tunnel. The swarm type is mainly controlled by the combined effects of excavation unloading and the presence of structure planes. Highlights: ● Microseismicity in 44 moderate and intense immediate rockburst development processes are analyzed. ● Microseismic sequences associated with immediate rockburst development processes follow certain patterns. ● Microseismic sequences can be divided into two types: fore-main and swarm shock microseismic sequences. ● The characteristics and mechanisms of formation of the microseismic sequences are different with each other.